Fungal biofactories for the formulation of nanocomposites for therapeutic applications - Gobi, Krishantinee; Norliana, Munir; Shoriya Aruni, Abdul Manaf; Aizi Nor Mazila, Ramli; Dailin, Daniel Joe; Nur Farzana, Ahmad Sanadi; Nor Hasmaliana, Abdul Manas (Springer Nature, 2025)
Fungal biofactories offer an innovative, eco-friendly platform for producing nanocomposites with therapeutic applications. Fungi possess remarkable metabolic capabilities, enabling them to synthesize a wide range of bioactive compounds, including enzymes, secondary metabolites, and biopolymers. These natural resources can be harnessed in the formulation of nanocomposites, which are nanoscale materials made from multiple components, typically offering enhanced properties like improved drug delivery, biocompatibility, and antimicrobial activity. This chapter introduces fungi as biofactories, structure and types of nanocomposites, mechanism of fungal nanoparticle formation, and therapeutic applications of fungal nanocomposites. The use of fungi in nanocomposite synthesis is particularly attractive due to their ability to reduce metal ions, stabilize nanoparticles, and produce biopolymers like chitosan and polysaccharides, which can act as natural matrices or coatings for nanomaterials. These fungal-derived nanocomposites can be designed to encapsulate therapeutic agents, including drugs, peptides, or biomolecules, allowing for controlled and targeted delivery in medical applications. Advantages, challenges, and future perspectives of fungal biofactories are also discussed. Fungal biofactories provide a sustainable approach, minimizing toxic chemicals commonly used in conventional nanomaterial synthesis and reducing environmental impact. Their versatility in producing various functional materials opens the door to developing advanced therapies, such as antimicrobial treatments, cancer therapies, and regenerative medicine. Overall, fungi represent a promising avenue for advancing nanotechnology in healthcare.